Critical overrun causations in marine projects. Issue 7 (19th April 2020) - Karami, Hamidreza; Olatunji, Oluwole Alfred
Abstract : Purpose: Delay causations in infrastructure projects are well reported in normative literature. However, very little is known regarding the environment-related causations which can assist in developing mitigation strategies. This study aims to examine critical causations of overruns in marine construction projects. Design/methodology/approach: A total of 73 delay factors, grouped into 16 themes, were identified from literature. Data relating to the significance of each factor were collected through a questionnaire survey administered to 151 respondents. A total number of 126 valid responses were retrieved. Reductionist methodology was used to identify the statistical significance of each delay causation. Findings: All 73 variables analysed in the study are significant, including communication issues amongst stakeholders, inadequate planning, safety issues, deficient technical instructions and inappropriate management approaches. Others include design and construction issues, issues with project organisational structures, political and cultural factors, environmental uncertainties and complexity in resource management. The study also found estimation errors, owner's attitude, financial issues, delay in approval processes, construction strategies and unavailability of appropriate technologies for the work as influencing factors. These findings are consistent with earlier studies on other forms of projects, but they further confirm that they are very relevant to marine projects. Research limitations/implications: Due to the diversity of marine projects, overrun factors are likely to manifest in different ways in varying project circumstances. In addition, economics, technologies and local legislation often influence project situations differently. Practical implications: The implications of these findings will assist in growing the practicality of scheduling and contract administration theories in marine projects. Although delay causations that have been reported in normative literature are relevant to marine construction, however, some of the causations are more severe in marine projects. It is important that planners and project stakeholders are mindful of this such that they can develop their expectations to tolerate variability rather than trade impracticable blames. Originality/value: Determining delay factors specific to marine construction projects assists stakeholders and project management community in developing dedicated strategies applicable in scheduling to prevent and correct obstructions caused by overruns. Since projects are different in types and sizes, delay observations cannot be generalised.